Production of extracellular enzymes by different isolates of Pochonia chlamydosporia - Esteves, Ivania; Peteira, Belkis; Atkins, Simon D.; Magan, Naresh; Kerry, Brian R. (Elsevier, 2009)
For the first time, the specific activities of chitinases, esterases, lipases and a serine protease (VCP1) produced by different isolates of the nematophagous fungus Pochonia chlamydosporia were quantified and compared. The isolates were grown for different time periods in a minimal liquid medium or media supplemented with 1 % chitin, 0.2 % gelatin or 2 % olive oil. Enzyme-specific activities were quantified in filtered culture supernatants using chromogenic p-nitrophenyl substrates (for chitinases, lipases and esterases) and a p-nitroanilide substrate (to measure the activity of the proteinase VCP1). Additionally, information on parasitic growth (nematode egg parasitism) and saprotrophic growth (plant rhizosphere colonisation) was collected. Results showed that the production of extracellular enzymes was influenced by the type of medium (p < 0.05) in which P. chlamydosporia was grown. Enzyme activity differed with time (p < 0.05), and significant differences were found between isolates (p < 0.001) and the amounts of enzymes produced (p < 0.001). However, no significant relationships were found between enzyme activities and parasitic or saprotrophic growth using Kendall's coefficient of concordance or Spearman rank correlation coefficient. The results provided new information about enzyme production in P. chlamydosporia and suggested that the mechanisms which regulate the trophic switch in this fungus are complex and dependent on several factors.
Keywords: Chitinases; Enzyme activity; Esterases; Kendall's coefficient of concordance; Lipases; p-nitrophenyl substrates; Pochonia chlamydosporia; Proteases; Spearman rank correlation coefficient